2021
DOI: 10.3389/fgene.2021.694777
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Signature Genes Associated With Invasiveness and the Construction of a Prognostic Model That Predicts the Overall Survival of Bladder Cancer

Abstract: Background: Bladder cancer has become the tenth most diagnosed cancer worldwide. The prognosis has been shown to differ between non-muscle invasive bladder cancer (NMIBC) and muscle invasive bladder cancer (MIBC). We aimed to identify signature genes that are associated with the invasiveness and survival of bladder cancer and to identify potential treatments.Methods: We downloaded gene expression profiles of bladder cancer from the Gene Expression Omnibus database to identify differentially expressed genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Due to BLCA having no obvious symptoms in the early stage, the difficulty of diagnosis is increased. In addition, high recurrence and metastasis rates contribute to the low 5-year overall survival of BLCA patients, which has become a major challenge for global health [ 20 ]. Up to now, the main treatment for BLCA is surgery, chemotherapy, and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to BLCA having no obvious symptoms in the early stage, the difficulty of diagnosis is increased. In addition, high recurrence and metastasis rates contribute to the low 5-year overall survival of BLCA patients, which has become a major challenge for global health [ 20 ]. Up to now, the main treatment for BLCA is surgery, chemotherapy, and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that more recruitment of naïve M0 macrophages is associated with early LNM, which could prevent T cells from attacking tumor cells and secrete growth factors promoting tumor angiogenesis 48,49 . T follicular helper cells might contribute to the maintenance of a protective immune response, which was proved to be associated with better prognosis in BC 50,51 . Furthermore, we observed higher expression levels of CTLA4 and PDCD1 in low‐risk group, suggesting BC patients with low risk points based on OS classifier might benefit more from immunotherapy 52 .…”
Section: Discussionmentioning
confidence: 59%
“…48,49 T follicular helper cells might contribute to the maintenance of a protective immune response, which was proved to be associated with better prognosis in BC. 50,51 Furthermore, we observed higher expression levels of CTLA4 and PDCD1 in low-risk group, suggesting BC patients with low risk points based on OS classifier might benefit more from immunotherapy. 52 Collectively, these results explained the possible mechanisms from the perspective of tumor biological and immune function and further corroborated the validity of our risk classifiers for OS and CSS.…”
Section: Discussionmentioning
confidence: 69%
“…Besides, we used multiple omics data such as genomics, transcriptomics to make the analysis more in-depth and complete. Compared with many previous reported signatures ( Sun et al, 2021a ; Sun et al, 2021b ; He et al, 2021 ; Yan et al, 2021 ), the predictive power of TMsig is more outstanding. Besides, the TMSig scoring system we constructed can effectively assess the immune profile of patients with urothelial cancer and predict patient prognosis, which we have validated with a sample of 1025 cases.…”
Section: Discussionmentioning
confidence: 76%